2019
DOI: 10.1088/1367-2630/ab2b00
|View full text |Cite
|
Sign up to set email alerts
|

Practical decoy-state method for twin-field quantum key distribution

Abstract: Twin-field (TF) quantum key distribution (QKD) represents a novel QKD approach whose principal merit is to beat the point-to-point private capacity of a lossy quantum channel, thanks to performing single-photon interference in an untrusted node. Indeed, recent security proofs of various TF-QKD type protocols have confirmed that the secret key rate of these schemes scales essentially as the square root of the transmittance of the channel. Here, we focus on the TF-QKD protocol introduced by Curty et al, whose se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 47 publications
2
56
1
Order By: Relevance
“…Note added-Recently, we found that [51,52] discussed the finite-key size effect and [53,54] discussed the security of TF-QKD under intensity fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…Note added-Recently, we found that [51,52] discussed the finite-key size effect and [53,54] discussed the security of TF-QKD under intensity fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…This is clear from figure 2, where we plot the secret key rate assuming that Alice and Bob use the same set of two, three and four decoy intensities. The plots are obtained by using the analytical yields bounds for the symmetric-intensities scenario derived in [28]. The experimental parameters used for the simulations are given in table 1 and the corresponding channel model is given in appendix A.…”
Section: Symmetric Intensitiesmentioning
confidence: 99%
“…Moreover, the practical feasibility of this scheme has been recently demonstrated in [24,25,27]. A complete analysis of the symmetric scenario where both users use the same signal intensities and analytically estimate the yields using the same decoy intensity settings was performed recently in [28]. However, using the same set of intensities is an optimal strategy only when the quantum channels connecting the users to the central node have approximately the same transmittance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reducing the assumption on the devices) [9-14], but at the same time are also implementable with today's technology [15][16][17][18]. In this context, a protocol which recently received great attention is the Twin-Field (TF) QKD protocol originally proposed by Lucamarini et al [19], further developed to prove its security [20][21][22][23][24][25][26][27] and experimentally implemented [28][29][30][31]. Indeed, the TF-QKD protocol relies only on single-photon interference occurring in an untrusted node, making it a measurement-device-independent (MDI) QKD protocol capable of overcoming the repeaterless bounds [32,33].In a scenario where several users are required to share a common secret key, one can for instance perform bipartite QKD protocols between pairs of users and then use the secret keys established in this way to encode the final common secret key.…”
mentioning
confidence: 99%